2021
DOI: 10.1177/0748233721996578
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular damage associated with subchronic exposure to the glyphosate herbicide in Wistar rats

Abstract: Glyphosate is the most widely used herbicide in the world. Although some studies have shown cardiac electrophysiological changes associated to glyphosate, the histopathological changes that this herbicide may cause in the cardiovascular system are not yet established. The aim of this study was to evaluate the cardiovascular effects of subchronic oral and inhalation exposure to the glyphosate herbicide in rats. Eighty albino Wistar rats were distributed into eight groups (five males and five females/group): inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, there was no dose-and exposure route-dependent alteration of the right and left ventricle thicknesses or in the collagen density. 154 Oral administration of GLP and Roundup significantly increased the urinary level of homocysteine, a risk factor for CVD, related to a deviated Prevotella sp. abundance in the gut.…”
Section: Preclinical Studies Of Glp Impact On the Endocrine And Repro...mentioning
confidence: 99%
“…However, there was no dose-and exposure route-dependent alteration of the right and left ventricle thicknesses or in the collagen density. 154 Oral administration of GLP and Roundup significantly increased the urinary level of homocysteine, a risk factor for CVD, related to a deviated Prevotella sp. abundance in the gut.…”
Section: Preclinical Studies Of Glp Impact On the Endocrine And Repro...mentioning
confidence: 99%
“…Based on toxicity tests conducted by the patent holder of GLY (i.e., Monsanto) in the 1970 and 1980 s, GLY was described as “virtually nontoxic” to animals and humans [ 12 ]. However, additional studies have found that GLY could be toxic to multiple organs, including but not limited to nephrotoxicity [ 13 ], hepatotoxicity [ 14 ], gastrointestinal [ 15 ], cardiovascular [ 16 ], respiratory [ 17 ], and reproductive systems [ 18 ]. The liver, the second most susceptible organ to GLY, has also been demonstrated in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…14 GLY exposure, indicating the early stages of atherosclerosis. 15 Based on lipidomic studies, GLY poses potential health risks, including atherosclerosis. 16 However, investigations into the underlying mechanisms of atherosclerosis caused by GLY are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…GLY has been observed to contribute to atherosclerosis. Studies have shown a significant incidence of fatty streak development in rats after GLY exposure, indicating the early stages of atherosclerosis . Based on lipidomic studies, GLY poses potential health risks, including atherosclerosis .…”
Section: Introductionmentioning
confidence: 99%